Sphingosine-1-phosphate is increased in patients with idiopathic pulmonary fibrosis and mediates epithelial to mesenchymal transition. Issue 2 (21st November 2011) - Milara, Javier; Navarro, Rafael; Juan, Gustavo; Peiró, Teresa; Serrano, Adela; Ramón, Mercedes; Morcillo, Esteban; Cortijo, Julio
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is characterised by the aberrant epithelial to mesenchymal transition (EMT) and myofibroblast accumulation. Sphingosine-1-phosphate (S1P) and sphingosine kinase 1 (SPHK1) have been implicated in lung myofibroblast transition, but their role in EMT and their expression in patients with IPF is unknown. Methods and results: S1P levels were measured in serum (n=27) and bronchoalveolar lavage (BAL; n=15) from patients with IPF and controls (n=30 for serum and n=15 for BAL studies). SPHK1 expression was measured in lung tissue from patients with IPF (n=12) and controls (n=15). Alveolar type II transformation into mesenchymal cells was studied in response to S1P (10 −9 –10 −5 M). The median (IQR) of S1P serum levels was increased in patients with IPF (1.4 (0.4) μM) versus controls (1 (0.26) μM; p<0.0001). BAL S1P levels were increased in patients with IPF (1.12 (0.53) μM) versus controls (0.2 (0.5); p<0.0001) and correlated with diffusion capacity of the lung for carbon monoxide, forced expiratory volume in 1 s and forced vital capacity (Spearman's r=−0.87, −0.72 and −0.68, respectively) in patients with IPF. SPHK1 was upregulated in lung tissue from patients with IPF and correlated with α-smooth muscle actin, vimentin and collagen type I (Spearman's r=0.82, 0.85 and 0.72, respectively). S1P induced EMT in alveolar type II cells by interacting with S1P2 and S1P3, as well as by the activation of p-Smad3, RhoA-GTP, oxidative stress and transforming growth factor-β1 (TGF-β1) release. Furthermore, TGF-β1-induced EMT was partially conducted by the S1P/SPHK1 activation, suggesting crosstalk between TGF-β1 and the S1P/SPHK1 axis. Conclusions: S1P is elevated in patients with IPF, correlates with the lung function and mediates EMT.